Network disruption detected in NC (New Caledonia) - Voidly (2026)
CRITICAL severity disruption detected in New Caledonia. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: NC-2026-0001
Keywords: internet disruption; NC; disruption; critical